Travelling tournament problem and its NHL application - Ivanič, Leon; Borovička, Adam; Fábry, Jan, 1967-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This bachelor thesis focuses on the overview and application of the travelling tournament problem with a specific focus on its application to the National Hockey League. It provides a theoretical overview of the problem, its formal definition, variations and its complexity. The travelling tournament problem, which can be viewed as an extension of the better-known traveling salesman problem, aims to optimize sports tournament scheduling by minimizing travel distances. The thesis is structured in two main sections: the first discusses the theoretical aspects of the problem, including its computational complexity and various solving techniques. The second part applies these methodologies to the National Hockey League, proposing a model that reduces the total number of games and travel distances, potentially decreasing costs and player fatigue.
Vedoucí práce: Adam Borovička
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor bakal. práce]; bakalářské práce; bachelor's theses